Yeast Cytosine Deaminase Mutants with Increased Thermostability Impart Sensitivity to 5-Fluorocytosine - Stolworthy, Tiffany S. (2008)
Prodrug gene therapy (PGT) is a treatment strategy in which tumor cells are transfected with a 'suicide' gene that encodes a metabolic enzyme capable of converting a nontoxic prodrug into a potent cytotoxin. One of the most promising PGT enzymes is cytosine deaminase (CD), a microbial salvage enzyme that converts cytosine to uracil. CD also converts 5-fluorocytosine (5FC) to 5-fluorouracil (5FU), an inhibitor of DNA synthesis and RNA function. Over 150 studies of cytosine deaminase-mediated PGT applications have been reported since 2000, all using wild-type enzymes. However, various forms of cytosine deaminase are limited by inefficient turnover of 5FC and/or limited thermostability. In a previous study we stabilized and extended the half-life of yeast cytosine deaminase (yCD) by repacking of its hydrophobic core at several positions distant from the active site. Here we report that random mutagenesis of residues selected based on alignment with similar enzymes, followed by selection for enhanced sensitization to 5FC, also produces an enzyme variant (yCD-D92E) with elevated T(m) values and increased activity half-life. The new mutation is located at the enzyme's dimer interface, indicating that independent mutational pathways can lead to an increase in the temperature that induces protein unfolding and aggregation in thermal denaturation experiments measured by circular dichroism spectroscopy, and an increase in the half-life of enzyme activity at physiological temperature, as well as more subtle effect on enzyme kinetics. Each independently derived set of mutations significantly improves the enzyme's performance in PGT assays both in cell culture and in animal models.